"I am interested in the metaphysics of being and existence": Chigozie Obioma in conversation with Kunle Ajibade. Issue 2 (4th May 2019) - Ajibade, Kunle
Abstract: On Sunday, 24 March 2019, P.A.G.E. Book Connoisseurs organized an evening of reading and conversation with Chigozie Obioma whose second novel, An Orchestra of Minorities, was just published in Nigeria by Parresia. It was a very rewarding encounter with Obioma, who was born in Akure, Ondo State, to an Igbo family of 12 children. He read English Literature at Cyprus International University (CIU), Northern Cyprus. Because he made a first class in his set, he was chosen as the student commencement speaker on 23 June, 2011. In his speech, Obioma spoke eloquently about the necessity for courage, diligence, hard-work, and gratitude. He made a solemn promise to make good use of all he had learnt at CIU. As a story-teller, he has been steadily fulfilling that promise. He was 27 years old in 2015 when his first novel, The Fishermen, was shortlisted for the Man Booker Prize. Among other prizes, the novel has won NAACP Image Award for Outstanding Literary Work, The Los Angeles Times Award for First Fiction, and Nebraska Book Award for Fiction. Before then, he was in Ledig House in New York for a residency and at the University of Michigan, Ann Arbor, Michigan, where he completed an MFA in creative writing. He writes occasionally for The Guardian of London and New Statesman, among other publications. Chigozie Obioma is an Assistant Professor of Literature and Creative Writing at the University of Nebraska-Lincoln, USA. In the course of our conversation, Professor Wole Soyinka, the 1986 Nobel Laureate in Literature, made a video call to the gathering, congratulating the author on his second novel, and his literary achievements so far. Obioma was grateful for Soyinka's kind words. The edited transcript has been supplemented with an earlier email interview conducted on 10 March 2019.